Preparation of Tariff Based on Unit Cost of Surgical Action in Balung Hospital Using Activity Based Costing (ABC) - Sri Wahyuni; Sri Hernawati; Sebastiana Viphindrartin (Humanistic Network for Science and Technology (HNST), 2018)
RSD Balung is a BLUD hospital, but the tariff determination had not been based on unit cost including the operation in the Installation of Hospital Operation Room Service Operations continue to show an increased, so operational expenses were increased. In JKN, there were several surgical actions that have a tariff difference that harms the hospital. The tariff claimed by hospital to BPJS was not as expected because the nominal tariff was less. The purpose of this research was to arrange tariff based on unit cost of operation cost action of room installation room of RSD Balung with Activity Based Costing (ABC) method. This research was a descriptive quantitative. The unit of analysis of this research was the Operation Room in RSD Balung by looking at the cost and service component of the service or the action to be done the operational action tariff analysis. Respondent was taken by pusposive sampling. The number of respondents in this study were 13 people. At the service of BPH, SC, and cataract in Operation Room RSD Balung there were difference of tariff either from BLUD tariff, tariff based on unit cost, and INA CBGs tariff. This difference was particularly evident from BPH services. This service was harming RSD Balung. While in SC and Cataract service, unit cost tariff was lower than BLUD tariff. Keywords: Unit cost, Tariff, BLUD, Operation room, INA-CBG’s